Refugee youth: migration, justice and urban space - De Backer, Mattias; Hopkins, Peter; Liempt, Ilse van; Finlay, Robin; Kirndörfer, Elisabeth; Kox, Mieke; Benwell, Matthew C.; Hörschelmann, Kathrin (Bristol University Press, 2024)
"Telling the stories of young refugees in a range of international urban settings, this book explores how newcomers navigate urban spaces and negotiate multiple injustices in their everyday lives. This innovative edited volume is based on in-depth, qualitative research with young refugees and their perspectives on migration, social relations and cultural spaces. The chapters give voice to refugee youth from a wide variety of social backgrounds, including insights about their migration experiences, their negotiations of spatial justice and injustice, and the diverse ways in which they use urban space" --